Does Surgical Specialty Impact Mandibular Fracture Outcomes?. Issue 3 (May 2021) - Sun, Alexander; Nguyen, Kevin; Mehta, Sumarth K.; Allam, Omar; Park, Kitae Eric; Alperovich, Michael
Abstract : Purpose: Maxillofacial trauma is treated by two medical specialties, plastic surgery (PRS) and otolaryngology (ENT). Differences in training exposure and practice patterns exist between specialties, but their respective outcomes have never been compared. Methods: Mandible fracture data were reviewed from the National Surgical Quality Improvement Program from 2005 to 2016. Demographics variables, repair types, and adverse outcomes were compared between PRS and ENT. Results: From 2005 to 2016, one thousand two hundred eighty-two cases were identified with 756 cases managed by ENT and 526 cases managed by PRS. Mean patient age was 34.6 years for both specialties ( P  = 0.95). Patient demographics between both cohorts were not statistically different except for higher rates of hypertension among ENT patients (10.2% for ENT versus 6.7% for PRS, P  = 0.027) and higher rates of smoking history among PRS patients (46.8% versus 52.3%, P  = 0.055). Mean operative time (131.3 versus 124.0 min, P  = 0.090) had a trend toward being longer for ENT and mean length of stay (1.3 versus 2.0, P  = 0.002) was significantly longer for PRS. Despite a greater proportion of high ASA class patients in the ENT group ( P  = 0.012 ) and patients with dirty/infected wounds in the PRS group ( P  = 0.013 ), there were no significant differences in 30-day readmission rates, 30-day reoperation rates, or wound infection rates. Conclusions: No significant differences in 30-day readmission rates, reoperation rates, or wound infection rates for mandible fracture management exist between specialties. Despite differences in training between PRS and ENT, both specialties have comparable perioperative outcomes for mandible fracture management. Abstract : Supplemental Digital Content is available in the text